Manufacturing Planning and Control Practices in the Malaysian Manufacturing Industry - Andrew Munot, Magdalene (2001)
The marketplace in which manufacturing firms are operating becomes more competitive. The Malaysian manufacturers become more internationally competitive by outperforming their international competitors in terms of one or more of the competitive priorities. The previous studies show that the MPC practices of manufacturing firms are essential for achieving and leading to the success of the companies' performance and competitiveness. Currently there is lack of internationally published studies on the use of MPC practices in the Malaysian manufacturing industries, particularly studies on the extensiveness of MPC practices usage. It is very important to assess the current trend of MPC practices of the Malaysian manufacturers in order to establish how extensive they are using the MPC practices to meet the competitive demand of the marketplace. The sample population was identified and selected from the Standard and Industrial Research Institute of Malaysia (SlRIM) 1999 Directory. The current information on MPC practices were gathered using the modified version of the Wbybark and Rho (1993) survey questionnaire from. the manufacturing firms across several industries. The survey questionnaires were distributed via mail to 870 manufacturing firms scattered all over Malaysia. Only, 86 manufacturers responded to this study, yielding a response rate of 9.9 per cent The information provided by the manufacturers was analysed using the Statistical Package for the Social Science (SPSS). The statistical data analysis shows that the manufacturers are customer-driven and responsive. They are extensively using a set of MPC practices that have been identified as essential for achieving and leading to the success of the companies' performance and competitiveness. They are also using the approaches for MPC practices which are similar to those used in other countries. Based on the Bivariate Correlations analysis, the factors taken into consideration are different depending on the specific MPC practice. The non-parametric Mann Whitney test, shows that there are differences due to firm size in several areas of the approaches for MPC practices. For further improvement of their MPC practices and competitiveness, the Malaysian manufacturers are advised to use the approaches comprehensively. In future studies, more manufacturers should involve themselves. In addition, future studies should also be done on assessing the companies' performance and competitiveness.